Oral hygiene level of children with cerebral palsy - Soekamto, Debrina Mayasari; Musnamirwan, Iwan Ahmad; Sasmita, Inne Suherna (Padjadjaran Journal of Dentistry, 2010)
Introduction: Dental and oral hygiene is important in supporting oral health in particular and general body health. Dental and oral hygiene can be maintained by controlling plaque. The aim of the study was to obtain data on the level of dental and oral hygiene in cerebral palsy children in the Sekolah Luar Biasa Bagian D Yayasan Pembinaan Anak Cacat, Sukajadi, Bandung. Methods: The research method is descriptive. Samples were obtained by total sampling technique which has criteria for children under 18 years old. A total of 43 children were obtained from all cerebral palsy children. Data were obtained by clinical examination, to calculate the level of dental and oral hygiene, OHI-S from Green and Vermillion was used by applying disclosing solution on the tooth surface, with criteria: good if the OHI value = 0.1-1.2; mean if the value of OHI = 1.3-3.0; bad if the value of OHI = 3.1-6.0 . Result: The results showed that the average dental and oral hygiene of cerebral palsy children in the Sekolah Luar Biasa Bagian D Yayasan Pembinaan Anak Cacat, Sukajadi, Bandung was 3.27. Conclusion: Dental and oral hygiene in cerebral palsy children in Sekolah Luar Biasa Bagian D Yayasan Pembinaan Anak Cacat, Sukajadi, Bandung is included in the bad criteria.